On the Development of New Forensic Tools for Detection of Human Skin Prints - V. A. Vasil’ev; T. A. Ermakova; Yu. A. Druzhinin; I. B. Afanas’ev; Yu. T. Yudina (Теория и практика судебной экспертизы, 2022)
The article reviews the main physical and physicochemical factors influencing the three-component system “fingerprint powder – prints bearing surface – sweat and grease print substance”. The authors propose new model compositions of fingerprint powders considering the reviewed common patterns: non-magnetic and luminescent magnetic. The features of prints bearing surfaces and developed fingerprint powders have been evaluated by applying electronic microscopy methods (scanning and probe microscopy). The authors have proven that the use of nano- and ultra disperse materials in the developed compositions (carbon nanotubes and shungite) enables to vary the sorption and adhesive capacity of fingerprint powders, which allows detecting fingerprints on varying surfaces with high selectivity toward the sweat and grease print substance and contrasting effect.